The impact of SF3B1 mutations in CLL on the DNA-damage response - Raa, G. Doreen te; Hüllein, Jennifer; Jethwa, Alexander; Zenz, Thorsten (Leukemia, 2015)
Mutations or deletions in TP53 or ATM are well-known determinants of poor prognosis in chronic lymphocytic leukemia (CLL), but only account for approximately 40% of chemo-resistant patients. Genome-wide sequencing has uncovered novel mutations in the splicing factor sf3b1, that were in part associated with ATM aberrations, suggesting functional synergy. We first performed detailed genetic analyses in a CLL cohort (n=110) containing ATM, SF3B1 and TP53 gene defects. Next, we applied a newly developed multiplex assay for p53/ATM target gene induction and measured apoptotic responses to DNA damage. Interestingly, SF3B1 mutated samples without concurrent ATM and TP53 aberrations (sole SF3B1) displayed partially defective ATM/p53 transcriptional and apoptotic responses to various DNA-damaging regimens. In contrast, NOTCH1 or K/N-RAS mutated CLL displayed normal responses in p53/ATM target gene induction and apoptosis. In sole SF3B1 mutated cases, ATM kinase function remained intact, and γH2AX formation, a marker for DNA damage, was increased at baseline and upon irradiation. Our data demonstrate that single mutations in sf3b1 are associated with increased DNA damage and/or an aberrant response to DNA damage. Together, our observations may offer an explanation for the poor prognosis associated with SF3B1 mutations.